Comparative Studies On Culture Method, Biological Parameters, And Climbing Abilities Of Tropical Bed Bug, Cimex Hemipterus (F.) And Common Bed Bug, Cimex Lectularius L. (Hemiptera: Cimicidae) - Kim, Dae Yun (2017)
This thesis focuses on the effects of artificial and natural feeding system on the biological parameters of both common (Cimex lectularius Linnaeus) and tropical bed bugs (Cimex hemipterus [Fabricius]), and the climbing ability of both species on pitfall style monitoring traps. The feeding effectiveness of an artificial feeding system (Hemotek® membrane feeding system) for Cimex lectularius (Monheim [MH] and Sydney [SYD] strains) and C. hemipterus (Madam Mo [MM], Tanjung Tokong [TT], Queensland [QSL] and Kuala Lumpur [KL] strains) using two types of rabbit blood (defibrinated [Defibrinated Rabbit Blood, DRB] and heparinized [Heparinized Rabbit Blood, HRB]) were compared with natural feeding on a human host.